The effect of natural oil and natural rubber on shear and peel strength of Pressure Sensitive Adhesive (PSA) system employing expanded polystyrene (EPS) foam / Nur Azleen Azahari - Azahari, Nur Azleen (2008)
Investigate on the effect of different composition of ENR (Epoxidised Natural Rubber) and ESO (Epoxidised Soybean Oil) on peel and shear strength of PSA was measured. In this research, EPS were dissolved with styrene, ESO and ENR. Tests were performed using shear strength and peel strength test. Shear strength and peel strength were performed using PVC film, PET film, PP film and plywood that are cut into different dimension for each test. The highest value for shear strength of the adhesive is when the ENR are added at 10% to the adhesive that were bonded to all substrate. The highest shear strength of the adhesive is when the ESO was added at 1% and bonded to PVC substrate. For the peel strength, the highest value is when ENR added to the adhesive at 10% and bonded to the PVC substrate. Effect of ESO showed for peel strength of adhesive, the highest value are when ESO added to adhesive at 10% and bonded to the PET substrate. For all testing, the PVC produced greater bonding with the adhesive and PP gives the poor bonding with adhesive.